Experimental Study on Vibration Characteristics of Prestressed Concrete Beam. (2017) - Toyota, Yusuke; Hirose, Takeshi; Ono, Syuichi; Shidara, Kazuhisa
Abstract: In recent years, fractures in PC rods of expressway PC bridges have been reported in Japan. These breakages could lead to bridge collapse in a worst- case scenario. In our study, we have carried out vibration tests on a model PC beam to clarify how vibration characteristics of PC beams change when the applied prestress of the PC rod is lowered and develop a simple and effective method of checking PC bridge health. In the experiment, we used a PC beam that allow the degree of prestress to be changed and tested the beam applying forced vibration at first vibration mode. As a result, we saw that as prestress lowered, the natural frequency of PC beam lowered, but the vibration damping performance increased. The tendency of the results is close to that of the theoretical value, and therefore, the test results are considered valid. From the above, we can see that lowering of prestress caused by fractures of PC rod can be estimated by looking at the vibration characteristics of PC beams.